ICT Leadership Education for Agricultural Extension in Sri Lanka: Assessing a Technology Stewardship Training Program - Gow, Gordon A; Dissanayeke, Uvasara; Jayathilake, Chandana K; Kumarasinghe, Isuri; Ariyawanshe, Kumudu; Rathnayake, Sanduni (International journal of education and development using information and communication technology, 2020)
This article reports on a technology stewardship training program to promote ICT leadership development with agricultural extension practitioners in Sri Lanka. Researchers used a multimethod approach with a single embedded case study. Data were collected using a pre-course survey, formal course evaluation, classroom observation, and semi-structured interviews with participants. Kirkpatrick's four-level evaluation model was used to structure analysis of the results. Findings from this study show a positive response to technology stewardship training among agricultural extension practitioners in the course, that learning objectives of the course are achievable when offered as an in-service training program, that self-confidence with ICT is improved, and that some participants applied their learning in a post-course activity. Results from the study also raise a number of considerations for future course design in order to better support digital leadership development in practice. Technology stewardship training shows promise as a form of ICT leadership education for agricultural communities of practice in Sri Lanka and elsewhere. This article contributes to a better understanding of the role of social learning among communities of practice in agricultural extension services, and in contributing to effective use of ICT for agriculture development more broadly.